Flipped Classroom Approach in Increasing EFL Learners’ Higher-order Thinking Skills: An Overview (RETAIN, 2020)
Abstract New curriculum in Indonesia which is 2013 curriculum has differences with the previous curriculum or KTSP. It has transformed the style of teaching and learning activities from teaching centered learning to student centered learning. It also has different goals which are asking students to get deeper understanding of the key concept, or developing students’ lower-order thinking skills (LOTS), as well as getting competent demonstration of the twenty-first century skills, or developing students’ higher-order thinking skill (HOTS). To achieve the goals set by the 2013 curriculum and to consider changing models of teaching and learning activities, Flipped classroom approach can be an alternative choice for teachers to use when teaching English classes. Flipped classroom approach is a pedagogical approach which aimed to require the students to master the materials by themselves before discussing those with their teacher in a classroom. This paper will mainly focus on increasing students’ HOTS using the flipped classroom approach in English teaching. Keywords: Flipped classroom approach, higher-order thinking skills, HOTS, student centered approach, EFL learner, EFL.